VENOUS HYPOXEMIA AND CAPILLARY LEAK SYNDROME WITH THE PATIENTS WITH ABDOMINAL SEPSIS AT A HIGH MORTALITY RISK - Kursov, S.V. (World of Medicine and Biology, 2012)
64 patients with abdominal sepsis who had high initial estimation points according to the Acute Physiology And Chronic Health Evaluation-II were examined for the mixed venous blood saturation with oxygen and for the volumes of body fluid areas during the week after the operation. Venous hypoxemia has been shown to associate with an excessive fluid accumulation in the interiticium. The severity degree of venous hypoxemia was fully correspondent to the severity of edema syndrome. The correlation analysis has shown a strong feedback between the venous blood saturation with oxygen and the severity of capillary leak syndrome development. Performing a liquid resuscitation with different groups of up-to-date plasma substitutes revealed that the best effect for the capillary leak limitation was shown by hydroxyethylstarch derivatives.